2004
DOI: 10.1523/jneurosci.1140-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 1 Is Required for the Proliferation of Hippocampal Progenitor Cells and for Hippocampal Growth in Mouse

Abstract: Fibroblast growth factor receptor 1 (Fgfr1) is expressed at high levels by progenitor cells of the ventricular zone (VZ) within the hippocampal primordium. To investigate the role of Fgfr1 in these cells, in vivo Cre recombination of "floxed" Fgfr1 alleles was directed to cells of the radial glial lineage by using the human glial fibrillary acidic protein promoter. Radial glial-like cells of the hippocampal VZ are the progenitors of pyramidal neurons and granule cells of hippocampal dentate gyrus (DG). Mice ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(161 citation statements)
references
References 74 publications
12
149
0
Order By: Relevance
“…As expected, the GCE transgene targeted recombination to radial glial cells when induced during embryogenesis, consistent with previous findings using the hGFAPCre line (Malatesta et al, 2003;Ohkubo et al, 2004;Casper and McCarthy, 2006), whereas during the first postnatal week, GCE targeted recombination to GFAP ϩ /RC1 ϩ astroglial cells of various morphologies, but not in neurons or oligodendrocytes (Table 1). In the P8 SVZ, hippocampus, and cortex, nearly all reporter ϩ cells expressed LeX, an antigen also expressed by embryonic and adult NSCs (Capela and Temple, 2002) and the great majority were immunoreactive for GFAP ϩ and RC1, yet in each area we observed a small population (10 -20%) of unlabeled cells.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, the GCE transgene targeted recombination to radial glial cells when induced during embryogenesis, consistent with previous findings using the hGFAPCre line (Malatesta et al, 2003;Ohkubo et al, 2004;Casper and McCarthy, 2006), whereas during the first postnatal week, GCE targeted recombination to GFAP ϩ /RC1 ϩ astroglial cells of various morphologies, but not in neurons or oligodendrocytes (Table 1). In the P8 SVZ, hippocampus, and cortex, nearly all reporter ϩ cells expressed LeX, an antigen also expressed by embryonic and adult NSCs (Capela and Temple, 2002) and the great majority were immunoreactive for GFAP ϩ and RC1, yet in each area we observed a small population (10 -20%) of unlabeled cells.…”
Section: Discussionsupporting
confidence: 90%
“…To evaluate whether FGF-2 overexpression changed FGF receptor density, we used immunohistochemistry to analyze the distribution of FGFR1, the FGF receptor subtype most expressed in the hippocampus (Ohkubo et al, 2004). Consistent with previous reports in rats and humans Weickert et al, 2005), FGFR1 immunoreactivity was found in putative pyramidal neurons of CA1, CA2 and CA3 pyramidal region in WT mice.…”
Section: Expression Of the Fgf-2 Transgene In The Brainsupporting
confidence: 77%
“…For instance in proliferating brain stem cells FGFR1 is cytoplasmic whereas in differentiating neural cells FGFR1 accumulates in the cell nucleus (Stachowiak et al, 2012a). In agreement with this dual distribution, brain‐targeted FGFR1 knockout impairs both the cell proliferation and differentiation (Pirvola et al, 2002; Ohkubo et al, 2004) which may reflect the loss of FGFR1 signaling at the cell surface and the INFS, respectively (Stachowiak et al, 2012b). …”
Section: Constitutive Plasma Membrane and Regulated Nuclear Targetingmentioning
confidence: 78%